Texts from UHR - Dahlberg, Simon; Language Council of Sweden, Institute for Language and Folklore (Institute for Language and Folklore, 2020)
Parallel texts received directly from the agency. The files that were downloaded were all pdf docx files. The txt files that are available are the result of saving to another file format (txt) in Word.

Texter mottagna direkt från UHR.

Parallella texter erhållna direkt från myndigheten. De filer som mottogs var i docx-format. De filer som finns tillgängliga i txt-format är ett resultat av sparning till nytt filformat (txt) i Word.
Texter från Universitets- och högskolerådet
Keywords: public administration; offentlig förvaltning; Higher and further education; Gymnasial och högre utbildning; SOCIAL WELFARE POLICY AND SYSTEMS; SOCIAL VÄLFÄRDSPOLITIK OCH VÄLFÄRDSSYSTEM; Social Sciences; Samhällsvetenskap; Educational Sciences; Utbildningsvetenskap; Languages and Literature; Språk och litteratur